Urban watershed eutrophication state monitoring using aquatic plant based technology - Othman, Rashidi; Hanifah, Nurul Azlen; Wan Muhamad, Wan Naimatul Asiah (2014)
Eutrophication is always associated with excess nutrients of nitrogen and phosphorus. Excess nutrients can trigger undesirable eutrophication, resulting in unhealthy algal blooms, spreading of certain aquatic macrophytes, depletion of oxygen and loss of key species, resulting in widespread degradation of many freshwater ecosystems. Runoff from agricultural fields, field lots, urban lawns, untreated, or partially-treated, domestic sewage and golf courses are among the main sources of these nutrients. Eutrophication of inland waters is currently one of the most prevalent environmental problems in lakes all over the world including Malaysia. This study was carried out to determine the levels of Nitrate (NO3), Nitrite (NO2) and Phosphorus (PO4). All species (Lemna minor, Hydrilla verticillata, Typha latifolia, Nymphaea lotus, Ipomomea aquatica, Eichhornia crassipes, Spirodella polyrhiza, Neptunia oleracea, Salvinia natans and Pistia stratiotes) were detected with high level of phosphate at level III which is polluted at all localities (Selangor, Pahang and Kelantan). Meanwhile, nitrate concentration at all localities is found to be under Class I which is natural water level. In conclusion, the most reliable phytoindicator for overall experiment were L.minor, E.crassipes and S.polyrhiza. It is proven that every floater aquatic plant species that has been tested was confirmed as potential phytoindicator to detect eutrophication in unhealthy aquatic ecosystem. This clearly demonstrates that freshwater environment with abundance of invasive macrophyte species can have an important influence and indication on the accumulation of nutrients content.